HRYHORII ARTYNOV - THE CREATOR OF THE ARCHITECTURAL HISTORY OF VINNITSIA - Yaroshchuk, Inna; Vlasyuk, Polina (Sworld-Us Conference proceedings, 2025)
Architecture is a silent chronicle recorded in the buildings, lines, and colors of cities, through which architects like Hryhorii Artynov express their opinions and shape the face of the city. Without his contribution, modern Vinnytsia would be completely